PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX TERHADAP NILAI PERUSAHAAN DAN KINERJA KEUANGAN PERUSAHAAN - Alvian Adhiprasetya; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2019)
This study aims to prove the effect of the Corporate Governance Perception Index on Company Values calculated using Tobin’s Q and the Company's Financial Performance measured using Return on Assets, Return on Equity, and Earnings per Share.The object of this study is all companies listed in the 2012-2015 Corporate Governance Perception Index ranking, which are assessed by the Indonesian Institute of Corporate Governance, which is an independent institution that conducts dissemination and development activities for Good Corporate Governance in Indonesia. The data collection method used in this study was purposive sampling, which is based on predetermined criteria. The research hypothesis was analyzed using descriptive statistical analysis methods and simple linear regression with control variables.The results of statistical tests in this study indicate that the independent variable does not affect the value of the company, but it affects the company's financial performance. Then in the t test the variable Corporate Governance Perception Index has no significant effect on firm value, but significantly influences the company's financial performance.